Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Let's solve the quadratic equation step-by-step, using the quadratic equation provided:
[tex]\[ x^2 - x - \frac{3}{4} = 0 \][/tex]
First, we'll rewrite the equation by moving \(-\frac{3}{4}\) to the other side:
[tex]\[ x^2 - x = \frac{3}{4} \][/tex]
Next, to make this suitable for completing the square, we add \(\left(\frac{1}{2}\right)^2\) to both sides. This is because the coefficient of \(x\) is \(-1\), and half of \(-1\) is \(-\frac{1}{2}\), so when squared, it is \(\left(\frac{1}{2}\right)^2\):
[tex]\[ x^2 - x + \left(\frac{1}{2}\right)^2 = \frac{3}{4} + \left(\frac{1}{2}\right)^2 \][/tex]
Calculating the right-hand side:
[tex]\[ x^2 - x + \frac{1}{4} = \frac{3}{4} + \frac{1}{4} \][/tex]
[tex]\[ x^2 - x + \frac{1}{4} = 1 \][/tex]
The left-hand side is now a perfect square trinomial:
[tex]\[ (x - \frac{1}{2})^2 = 1 \][/tex]
To find \(x\), we take the square root of both sides:
[tex]\[ x - \frac{1}{2} = \pm 1 \][/tex]
This gives us two equations to solve:
[tex]\[ x - \frac{1}{2} = 1 \quad \text{or} \quad x - \frac{1}{2} = -1 \][/tex]
Solving these:
[tex]\[ x = 1 + \frac{1}{2} = \frac{3}{2} \][/tex]
[tex]\[ x = -1 + \frac{1}{2} = -\frac{1}{2} \][/tex]
Therefore, the solutions to the quadratic equation \(x^2 - x - \frac{3}{4} = 0\) are:
[tex]\[ x = \frac{3}{2} \quad \text{and} \quad x = -\frac{1}{2} \][/tex]
From the given possible solutions:
- \(-\frac{1}{4}\)
- \(\frac{1}{2}\)
- \(\frac{3}{2}\)
- \(\frac{3}{4}\)
The correct solution provided by the options is \(\frac{3}{2}\).
Thus, the solution of \(x^2 - x - \frac{3}{4} = 0\) from the options given is:
[tex]\[ \boxed{\frac{3}{2}} \][/tex]
[tex]\[ x^2 - x - \frac{3}{4} = 0 \][/tex]
First, we'll rewrite the equation by moving \(-\frac{3}{4}\) to the other side:
[tex]\[ x^2 - x = \frac{3}{4} \][/tex]
Next, to make this suitable for completing the square, we add \(\left(\frac{1}{2}\right)^2\) to both sides. This is because the coefficient of \(x\) is \(-1\), and half of \(-1\) is \(-\frac{1}{2}\), so when squared, it is \(\left(\frac{1}{2}\right)^2\):
[tex]\[ x^2 - x + \left(\frac{1}{2}\right)^2 = \frac{3}{4} + \left(\frac{1}{2}\right)^2 \][/tex]
Calculating the right-hand side:
[tex]\[ x^2 - x + \frac{1}{4} = \frac{3}{4} + \frac{1}{4} \][/tex]
[tex]\[ x^2 - x + \frac{1}{4} = 1 \][/tex]
The left-hand side is now a perfect square trinomial:
[tex]\[ (x - \frac{1}{2})^2 = 1 \][/tex]
To find \(x\), we take the square root of both sides:
[tex]\[ x - \frac{1}{2} = \pm 1 \][/tex]
This gives us two equations to solve:
[tex]\[ x - \frac{1}{2} = 1 \quad \text{or} \quad x - \frac{1}{2} = -1 \][/tex]
Solving these:
[tex]\[ x = 1 + \frac{1}{2} = \frac{3}{2} \][/tex]
[tex]\[ x = -1 + \frac{1}{2} = -\frac{1}{2} \][/tex]
Therefore, the solutions to the quadratic equation \(x^2 - x - \frac{3}{4} = 0\) are:
[tex]\[ x = \frac{3}{2} \quad \text{and} \quad x = -\frac{1}{2} \][/tex]
From the given possible solutions:
- \(-\frac{1}{4}\)
- \(\frac{1}{2}\)
- \(\frac{3}{2}\)
- \(\frac{3}{4}\)
The correct solution provided by the options is \(\frac{3}{2}\).
Thus, the solution of \(x^2 - x - \frac{3}{4} = 0\) from the options given is:
[tex]\[ \boxed{\frac{3}{2}} \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.